Jesus feminist eaudiobook An invitation to revisit the bible's view of women. - Bessey, Sarah (Tantor Media, 2014)
For centuries, the role of women in the Church has been a subdued one, with many limitations. The time has come, argues Sarah Bessey—who has been called an "accidental grassroots voice for postmodern and progressive evangelical women"—to take a new look at Scripture and challenge old assumptions. In Jesus Feminist , Bessey shares her spiritual journey, which ranges from growing up in a post–gender-debate home to learning about the worldwide struggles of women and the obstacles even a well-meaning church can pose. Through disarmingly intimate storytelling, she tells how she grew to understand the story of God and the vastness of his work through women. Never one to shy away from the hard questions, Bessey engages critically with Scripture and church practices that are often used against full equality and shares how following Jesus made a feminist out of her. Filled with beauty, hard truth, and brave vulnerability, Jesus Feminist urges the Church to stop asking "man or woman" as a qualification for ministry and to start helping everyone find freedom in the fullness, hope, glory, and work of Christ.